Building optimistic perovskite-polymer composite solar cells: Feasible involvement of a BLP inclusion to efficiently stable perovskite films. (15th June 2023) - Buregeya Ingabire, Providence; Lei, Ning; Song, Lixin; Zhang, Pengyun; Chen, Shouwen; Du, Pingfan; Xiong, Jie
Abstract: The character of perovskite film sustains the tenable concern frustrating the construction of perovskite solar cells (PSCs) with both competent stability and acceptable photovoltaic performance. In the present study, quaternized poly(aryl ether sulfone)s-reinforced carbon nitride or organic-inorganic blend composite containing quaternized polymer (BLP) materials derived from quaternized poly(aryl ether sulfone)s or polymer of quaternary ammonium chloride (PQACl), and graphitic carbon nitride (sCN), is integrated into perovskite. The PQACl inclusion is a promising material which consists of a cationic quaternary ammonium and an anionic chloride ions. The sufficiently good amount of BLP inclusion in the perovskite system favors the crystal morphology, represses the generation of defects through sequestering the counter ions and reducing ions movements. Well-mannered investigations reveal that BLP inclusion extremely initiates hydrogen bonding interactions with the perovskite, which lowers charge carrier recombination. As a result, the most efficient PSC device processed with PVK-BLP4 film shows a PCE of 19.38% compared with 16.74% in the pure PVK. And the optimized device based on the exploration of a BLP inclusion maintains over 72% of the original efficiency after appropriately continuous 210h thermal handling at 85 °C under 40–50 RH% moisture. The fabrication of BLP-decorated perovskite films is an inspiring engineering for use in solar cells. Graphical abstract: Integrating a proper amount of organic-inorganic blend composite containing quaternized polymer (BLP) in the perovskite boosts the PSC device performance, together with amelioration in stability. Image 1 Highlights: The polymer materials are properly integrated into the perovskite active layer. Organic-inorganic blend composite materials into perovskite can significantly passivate the defects. The device handled with PVK-BLP4 film reveals an improvement in efficiency and stability. The device manipulation can be carried out in ambient air condition.